A Statistical Investigation of Factors Influencing the Magnetotail Twist at Mars. Issue 12 (16th June 2022) - DiBraccio, Gina A.; Romanelli, Norberto; Bowers, Charles F.; Gruesbeck, Jacob R.; Halekas, Jasper S.; Ruhunusiri, Suranga; Weber, Tristan; Espley, Jared R.; Xu, Shaosui; Luhmann, Janet G.; Harada, Yuki; Dubinin, Eduard; et al.
Abstract: The Martian magnetotail exhibits a highly twisted configuration, shifting in response to changes in polarity of the interplanetary magnetic field's (IMF) dawn‐dusk ( B Y ) component. Here, we analyze ∼6000 MAVEN orbits to quantify the degree of magnetotail twisting ( θ Twist ) and assess variations as a function of (a) strong planetary crustal field location, (b) Mars season, and (c) downtail distance. The results demonstrate that θ Twist is larger for a duskward (+ B Y ) IMF orientation a majority of the time. This preference is likely due to the local orientation of crustal magnetic fields across the surface of Mars, where a + B Y IMF orientation presents ideal conditions for magnetic reconnection to occur. Additionally, we observe an increase in θ Twist with downtail distance, similar to Earth's magnetotail. These findings suggest that coupling between the IMF and moderate‐to‐weak crustal field regions may play a major role in determining the magnetospheric structure at Mars. Plain Language Summary: MAVEN magnetic field data are analyzed to understand factors that may influence the magnetotail structure at Mars. The Martian magnetotail lobes are observed to be twisted and the degree of this twist can vary. In this work, we calculate the degree of tail twist and monitor how it changes. To understand how the twist changes, we examine these variations as a function of Mars crustal field location, Mars season, and downtail distance away from Mars. Key Points: Mars' magnetotail can be twisted up to 60 deg away from its expected location based on interplanetary magnetic field (IMF) draping, much greater than Earth's tail twist MAVEN observations show that Mars' tail exhibits larger twisting for + B Y IMF orientation, compared to − B Y IMF Mars crustal magnetic fields may play a significant role in shaping the twisted structure of the Martian magnetotail